2015 Asia-Pacific Software Engineering Conference (APSEC) 2015
DOI: 10.1109/apsec.2015.40
|View full text |Cite
|
Sign up to set email alerts
|

Surveying the Corpus of Model Resolution Strategies for Metamodel Evolution

Abstract: Modeling languages evolve regularly. Companies need to maintain all those models that are used in running projects, which can cause these projects to fall back in their schedules. Since 10 years research addresses this issue with approaches for automating co-evolution. The dominant core of these approaches are model resolution strategies. They define 1) how models have to be changed in reaction to specific metamodel changes, 2) what degree of automation can be reached, and 3) to what extent the user can contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…Nonetheless, there seem to be common sources of error, when assessing whether a change type is breaking or non-breaking. For example, in [76] we found that misclassifications seem to stem from situations where special cases of change types are not considered. In consequence, we found change types that are treated by some approaches as non-breaking while other approaches treated them as breaking and provided resolution strategies [76] .…”
Section: Supported Benefit Classesmentioning
confidence: 94%
See 1 more Smart Citation
“…Nonetheless, there seem to be common sources of error, when assessing whether a change type is breaking or non-breaking. For example, in [76] we found that misclassifications seem to stem from situations where special cases of change types are not considered. In consequence, we found change types that are treated by some approaches as non-breaking while other approaches treated them as breaking and provided resolution strategies [76] .…”
Section: Supported Benefit Classesmentioning
confidence: 94%
“…Please note that the degree of automation is in literature often addressed with a classification of change types into "non-breaking", "breaking and resolvable" and "breaking and non-resolvable" change types. However, during this survey and a related one [76] we found some serious flaws in that classification and its application that made us reconsider its use.…”
Section: Supported Benefit Classesmentioning
confidence: 95%
“…A PartialChange concerns a model element (concernedElt). We list in the ChangePartialKind enumeration the following partial changes inspired from the work in the literature [32]: • A global change has a high priority; so, it is inserted at the top of the stChanges stack since it changes the whole structure of a viewpoint, and will be processed first. • A partial change:…”
Section: Activity 1: Detect Changesmentioning
confidence: 99%
“…However, coevolution approaches repair a particular type of inconsistencies w.r.t. metamodels conformance [19,20]. Here we focus on model repair.…”
Section: Related Workmentioning
confidence: 99%